Dichorionic twin pregnancy with sirenomelia and chromosomal anomaly in 1 fetus: A case report. Issue 1 (8th January 2021) - Ting, Yuan; Xue-Lan, Li; Chun-Bao, Wang; Ting, Zhang; Fen, Li; Zhen, Han
Abstract: Rationale: Sirenomelia is a rare congenital malformation that threatens fetal survivals. The cases in which twin with sirenomelia and chromosomal abnormality have been seldomly reported. We reported a dichorionic twin case in which one twin had sirenomelia, the other twin had a normal phenotype, and they had different chromosomal abnormalities. Patient concerns: The abnormal twin was found at 22 weeks by ultrasound. The sirenomelia fetus was complicated with a thoracic stenosis, enlarged rectum without anal opening, the absence of bilateral kidneys, a single umbilical artery, a single lower limb, the abnormal curvature of spine, double outlet of right ventricle, which were the indicatives of the chromosome detection. Diagnosis: The copy number variation of the sirenomelia fetus was detected as a deletion of 4.8Mb in 11p11.12-11q11. The co-twin was found with del(Y)(q11.223q11.23), which was as the same as his father's. The mother had normal chromosome. The parents had normal phenotypes. It was firstly reported a microdeletion with sirenomelia fetus. Interventions: There was no specific treatments for the twins. Outcomes: Intrauterine death of the sirenomelia fetus was found at 27 weeks and postnatal death after inevitable abortion happened to the co-twin. Lessons: Prenatal ultrasound was responsible for recognizing sirenomelia, and the detailed ultrasound scanning and chromosome detection should be done for the co-twin. The etiology of sirenomelia remains unclear, and genetic detection is also necessary for its pathogenesis research.